Characterisation of the biosand filter for E. coli reductions from household drinking water under controlled laboratory and field use conditions - Stauber, C E (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
More than a billion people in the developing world lack access to safe and reliable sources of drinking water. Point of use (POU) household water treatment technology allows people to improve the quality of their water by treating it in the home. One emerging POU technology is the biosand filter (BSF), a household-scale, intermittently operated slow sand filter. Laboratory and field studies examined Escherichia coli reductions achieved by the BSF. During two laboratory studies, mean E. coli reductions were 94% and they improved over the period of filter use, reaching a maximum of 99%. Field analysis conducted on 55 household filters near Bonao, Dominican Republic averaged E. coli reductions of 93%. E. coli reductions by the BSF in laboratory and field studies were less than those typically observed for traditional slow sand filters (SSFs), although as for SSFs microbial reductions improved over the period of filter use. Further study is needed to determine the factors contributing to microbial reductions in BSFs and why reductions are lower than those of conventional SSFs